Internship in palliative care : in the palliative care, pain therapy and rehabilitaion unit : Fondazione IRCCS - Istituto Nazionale dei Tumori, Milan, Italy : final report - Matos, Ana Leonor Vasconcelos Vilar Cadete de (2019)
The possibility to work for three months in Istituto Nazionale dei Tumori in Milan gave me the opportunity to develop practical skills in Palliative Care, which I felt I lacked. It also provided me the chance to work in a renowned institution, side by side with specialists with a vast experience in providing advanced holistic care to cancer patients. The opportunity was both appealing and challenging. My main goals were: to develop skills in the comprehensive assessment of pain and other symptoms from cancer and its treatment; to monitor patients for adequacy of symptom relief; to improve communication techniques mainly in illness understanding, prognosis and end of life; to learn more about clinical research in palliative care and if possible, to participate in clinical studies, and finally to integrate multidisciplinary teams in different settings of palliative care provision. During my 3 months’ internship in the Palliative Care, Pain Therapy and Rehabilitation Unit, I’ve worked in the Outpatient Clinics, Day Hospital, Hospice, Inpatient Consultation Team and Home Care Team, and I have also developed research work within the Department. I value this experience as it changed my perception of Palliative Care, and reassured me that this subject of medicine is rigorous, based on robust evidence, and has a remarkable impact in quality of life and survival of patients living with advanced illness. I’ve worked dedicatedly to this final report in order to describe, in the most realistic way, what drives me, which are my goals, and how I’ve achieved them during this internship. The research project concerning palliative sedation resulted in an article published in the Journal of Pain and Symptom Management. In the end, I feel that I’ve benefited immensely from this experience, gathering skills and competences to improve palliative care in my daily practice and to give my contribution to the delivery of top quality palliative care in my country.